The Multiplicative Effects of Personality Dimensions on Creative Behavior among Indonesian Radio Station Managers - Nugroho J. Setiadi; Anees Janee Ali; Rehana Aafaqi (Journal of Accounting, Business and Management (JABM), 2010)
The main purpose of the article is to increase understanding in evidence the multiplicative effects of personality dimensions on creativity. Using five-factor inventory (NEO-FFI) as input model of individuals creativity, the authors identified that among personality dimensions are synergistically related to creative performance. Among a sample of 283 Indonesian radio station managers, the authors hypothesized and found that some personality dimensions were significantly related to creative performance. The important findings also showed that Conscientiousness and Neuroticism have played a role synergistically to interact with other personality dimensions to predict highly creative performance.